ANALYSIS OF PERCENTAGE OF POWER LOSS FOR PHOTOVOLTAIC MODULE UNDER TEMPERATURE CONDITION IN KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
For optimal design and system planning, it is essential to assess the actual operating status of solar to determine the detrimental impact of power losses. The paper analyzes the power loss caused by photovoltaic (PV) modules under the temperature conditions of Kaduna State, Nigeria. The study conducted an outdoor experiment between 7:00 AM and 6:00 PM, with a 30-minute interval to evaluate the performance of the installed modules in real time.  The power output parameters and temperature of a monocrystalline and polycrystalline 120Watt PV panel were measured for three months, covering three seasons: August, January, and April. The experiment used two MASTECH MY64 digital multimeters and a temperature sensor (thermostat). The study found that the PV panel should reach its peak point between 11:00 AM and 2:30 PM, due to the angle of incident rays from the sun, high solar irradiance, and temperature. However, it was also observed that the heat generated by the PV panel in that region as a result of the panel's prolonged exposure to the sun negatively affected the output voltage and power generated. The results also showed that as the temperature increased, the current output increased but the voltage and power output decreased. The findings observed that every 1°C rise in temperature resulted in an average decrease of 0.51 watts (0.43%) for monocrystalline and 0.9 watts (0.78%) for polycrystalline during the solar peak. The study concluded that determining the actual working state of PV modules is crucial for an optimal design solution and improved system...
Keywords: Mono-crystalline PV module; polycrystalline PV module; power loss; solar photovoltaic energy; temperature sensor